Acute and chronic effects of stretching on balance: a systematic review with multilevel meta-analysis - Lohmann, Lars Hubertus; Zech, Astrid; Plöschberger, Gerit; Oraže, Manuel; Jochum, Daniel; Warneke, Konstantin (Frontiers in Medicine, 2024)
Balance is a multifactorial construct with high relevance in, e.g., everyday life activities. Apart from sensorimotor control, muscle strength and size are positively linked with balance performance. While commonly trained for via resistance training, stretch training has emerged as a potential substitution in specific conditions. However, no review has investigated potential effects of stretching on balance, yet.Methods: PubMed, Web of Science and Scopus were searched with inception to February, 2024. Studies were included if they examined acute and/or chronic effects of any stretching type against passive and/or active controls on balance parameters -without any populationrelated restrictions concerning sex/gender, age, health status, activity level. Methodological quality was assessed using PEDro scale. Meta-analyses were performed if two or more studies reported on the same outcome. Certainty of evidence was determined based on GRADE criteria.Results: Eighteen acute and eleven chronic effect studies were included. Stretching studies exhibited significant improvements for sway parameters with eyes open against passive controls of moderate magnitude for chronic (ES: 0.63, p=0.047) and of small magnitude for acute studies (ES: 0.21, p=0.032). Most other subgroups against passive controls as well as actively-controlled comparisons resulted in trivial and/or non-significant effects.Even though some pooled effects slightly reached the level of significance, the overall results are biased by (very) low certainty of evidence (GRADE criteria downgrading for risk of bias, imprecision, publication bias). Moderators suggested by literature (strength, muscle size, flexibility, proprioception) were rarely assessed, which prevents conclusive final statements and calls for further, high quality evidence to clarify potential mechanisms behind, if any exist.